Brain glucose utilisation in acquired childhood aphasia associated with a sylvian arachnoid cyst: recovery after shunting as demonstrated by PET. Issue 3 (March 1994) - De Volder, A G; Michel, C; Thauvoy, C; Willems, G; Ferrière, G
Abstract : Regional brain glucose utilisation was investigated with PET and fluorodeoxyglucose (FDG) in a case of epileptic aphasia (Landau-Kleffner syndrome) associated with a left sylvian arachnoid cyst. CT and MRI had failed to disclose any mass effect of the cyst on surrounding brain structures. Sequential metabolic measurements showed a comparable pronounced hypometabolism in cortical regions around the cyst, involving speech areas, and suggested mild but chronic compression of the developing brain. After placement of a cyst-peritoneal shunt system, significant metabolic improvement occurred in all cortical regions, especially the inferior frontal gyrus and the perisylvian area, with predominant residual deficit in the left superior temporal gyrus. These findings were correlated with a pronounced increase in word fluency and slower progress in verbal auditory comprehension. This report suggests that PET is able to evaluate the functional disturbances associated with expanding arachnoid cysts, and to follow the neurological improvement after drainage.